Improving virtual reality exposure therapy with open access and overexposure: a single 30-minute session of overexposure therapy reduces public speaking anxiety - Macdonald, Chris (Frontiers in Virtual Reality, 2024)
Public speaking anxiety is a prevalent issue with significant negative impacts. While virtual reality exposure therapy is an effective treatment, it currently has significant limitations. This study outlines the design process of a new VR platform that seeks to make virtual reality exposure therapy more effective and more accessible. To increase accessibility, the platform is open access and accessible via multiple devices and operating systems. To increase efficacy, the concept of overexposure therapy was developed: training in extreme scenarios that one is unlikely to encounter in real life. For example, on the platform, users can practice public speaking in a highly distracting stadium environment to a virtual reality audience of 10,000 photorealistic spectators. A singlesession experiment with 29 adolescents evaluated the platform's impact on public speaking anxiety, confidence, and enjoyment. Results showed significant improvements in all three measures. These findings suggest that this novel approach holds promise. The paper concludes by exploring limitations and areas for future research.